졸업예정 간호대학생의 자아존중감, 외모만족도, 취업스트레스가 삶의 질에 미치는 영향 - 문덕희(Duck-Hee Moon) (디지털콘텐츠학회논문지, 2019)
본 연구는 졸업예정 간호대학생의 자아존중감, 외모만족도, 취업스트레스, 삶의 질 정도와 상관관계를 확인하고 삶의 질에 영향을 주는 요인을 알아보고자 실시하였다. 간호대학생 143명을 대상으로 2019년 6월 1일부터 6월 15까지 설문조사 하였으며, 수집된 자료는 SPSS 20.0 프로그램을 이용하여 t-test, ANOVA, Scheffe test, Person’s correlation coefficients, 다중회귀분석 하였다. 자아존중감은 3.04, 외모만족도는 3.67, 취업스트레스는 2.72, 삶의 질은 3.46이었고 자아존중감, 외모만족도는 삶의 질과 유의한 양의 상관관계를 취업스트레스는 삶의 질과 음의 상관관계가 있었다. 삶의 질에 가장 유의한 영향을 준 것은 자아존중감이고 외에 성별, 교우관계, 취업스트레스였으며 설명력은 48.5%였다. 따라서 졸업예정 간호대학생의 삶의 질을 증진시키기 위해 자아존중감을 올려줄 수 있는 중재프로그램의 계획과 적용이 필요하다. The purpose of this study was to investigate the influence on self-esteem, appearance satisfaction and job-seeking stress of senior nursing students’ quality of life. Subjects were 143 nursing students. Data were collected by questionnaires from nursing students from June 1 to June 20, 2019. Data were analyzed using t-test, ANOVA, Scheffe test, Pearson correlation coefficients and multiple regression analysis. The degree of influence self-esteem was 3.04, appearance satisfaction was 3.67, job-seeking stress was 2.72 and quality of life was 3.46. Quality of life was positive correlated with both self-esteem and appearance satisfaction. Job-seeking stress was negative correlated with quality of life. The self-esteem, gender, satisfaction of relationship and job-seeking stress were identified as factors influencing quality of life. The model explained 48.5% of the variables. These results suggest that we need to develop a program in order to manage the quality of life of senior nursing students. KCI Citation Count: 6